Fertility, Health and Education of UK Immigrants: The Role of English Language Skills - Yu Aoki; Lualhati Santiago (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2015)
This paper aims to identify the causal effect of English language skills on fertility, health and education outcomes of immigrants in England and Wales. To estimate this causal effect, we use the instrumental variable estimation strategy where age at arrival in the United Kingdom (UK) is exploited to construct an instrument for language skills. The idea of exploiting age at arrival is based on the phenomenon that a person who is exposed to a new language within the critical period of language acquisition (i.e., childhood) learns the language more easily. This implies that immigrants who arrive in the UK at a young age have on average better English language skills than those who arrive when they are older. Using a unique individual-level dataset that links census and life event records for the population living in England and Wales at the 2011 Census, we find that better English language skills significantly delay the age at which a woman has her first child, lower the likelihood that she has a child in her teens, and decrease the number of children she gives birth to, but do not affect her children's birthweight and an individual's self-reported health. The impact on educational achievement is also considerable: better English skills significantly raise the probability of obtaining academic degrees and significantly lower the probability of having no qualifications.
Keywords: I10; I20; J13; 330; Language skills; fertility; health; education; natural experiment